Improving Postoperative Pediatric Recovery by Efficient Recovery Room Care—A Comprehensive Review - Lisa Korell; Frank Fideler (Children)
Background/Objectives: Efficient postoperative recovery room care in pediatric patients is crucial for optimizing perioperative safety, patient outcome, and effective pain management. However, this area is frequently underemphasized, leading to higher complication rates compared to the operating room, which in turn increases healthcare costs. Improving pediatric recovery room care offers a significant opportunity to enhance the quality and safety of perioperative pediatric care. From an economic perspective, this is prudent; however, more importantly, every child has the right to the highest attainable standard of health, as outlined by the United Nations. Key aspects of recovery room care include ensuring adequate staffing and equipment, while also prioritizing the child’s privacy and parental presence, both of which are crucial for enhancing patient well-being. A +multimodal approach to postoperative pain management is essential for minimizing fear and stress, alongside strict adherence to established guidelines for the management of postoperative nausea, vomiting, and emergence delirium. Furthermore, addressing risk factors such as hypothermia and airway complications, as well as promoting early intake of clear fluids, plays a crucial role in optimizing pediatric recovery. Organizational strategies such as quality improvement initiatives, structured handovers, standardized care protocols with checklists, continuous staff training, and well-defined discharge criteria are further essential components to reduce translational gaps and to enhance postoperative pediatric safety. Conclusions: Improving pediatric postoperative anesthetic care is a multifaceted challenge for all healthcare providers that can significantly enhance care quality and safety while also reducing costs. Success in this area requires addressing both structural and medical factors.